PENGARUH DEBT DEFAULT, FINANCIAL DISTRESS, OPINION SHOPPING DAN AUDIT TENURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Dea Izazi, Rizka Indri Arfianti (Jurnal Akuntansi, 2019)
Going concern is always linked with management capabilities in managing the company in order for the company to survive. The audit report with the modification of going concern is an indication that in the auditor's judgment there is a risk that the entity can not survive in the business world. Provision of going concern audit opinion by the auditors often addressed as bad news by the company, because it is alleged to cause the company to become bankrupt quickly. This study aims to examine the effect of debt default, financial distress, opinion shopping and audit tenure to the acceptance of going concern audit opinion. The sampling technique used in this study is purposive sampling with a total sample of 180 non-financial companies listed on the Indonesia Stock Exchange during the period of research year 2014-2016. Hypothesis testing of this research is done by logistic regression analysis using SPSS ver20. The result of this study shows that debt default and financial distress have significant value of 0,000 and 0,019, respectively. While audit tenure and opinion shopping have significant value of 0.000 and 0.0105, respectively. The conclusion of this study showed that debt default and financial distress are significantly affect on the acceptance of going concern audit opinion, while the opinion shopping and audit tenure are not significantly affect on the acceptance of going concern audit opinion.Keywords: Going Concern Audit Opinion, Debt Default, Financial Distress, Opinion Shopping, Audit Tenure